La necesidad de reformar el literal “e” en el art.145 de la ley orgánica de transporte terrestre, tránsito y seguridad vial, respecto a las sanciones de prisión para los conductores por el exceso de velocidad fuera de los rangos moderados sin causar daños humanos ni materiales - Cueva Carrión, María Patricia (2015)
In this thesis I found very important points regarding the subject of criminal law, Organic Law of Transport, Land, Traffic and Road Safety General Regulations for the Implementation of the Law on Transport, Land, Traffic and Road Safety, and as the fundamental principles of due process of law follows a brief summary of its contents. First start with definitions that help better understand about the definition of Punishment, Prison, Driver Vehicle, What is the speed range ?, What ?, which types of speed range, as well as those of Radar, Traffic Signal, Traffic, License, is the major theme of context. We also talked about its doctrine and its legal framework. The Organic Law on Land Transportation, Traffic and Road Safety, adopted by the National Assembly, which is published in the Official Gazette no. 398, dated 7 August 2008, is a modern legislation and a reform yet still it has shortcomings, for this reason at present and the respective reforms in the Criminal Code of Integral performed. Today for the various reforms being made to the laws and codes of our country, it is Law on Land Transportation, Traffic and Road Safety. It has practically run out of applicability, so a proposed amendment to the Organic Law of Land Transport, Traffic and Road Safety, regarding the sentence of imprisonment for drivers for speeding outside the moderate range proposed harmlessly human or material. This amendment to the Organic Law of Land Transport, Traffic and Road Safety is very important when applying a penalty of imprisonment to those who have not caused any damage and this is material or human and yet be brought after bars for three days in the company of people who if committed a crime; besides constitutional rights they are not being applied properly. The purpose of this paper is to describe the legal system with respect to prison for speeding motorists who violate the limits allowed in the streets and roads of our country, that being a relatively new subject in our country has been applied effectiveness due and drivers in general are unaware of their reach. Another of the highlights of the research work are surveys and interviews to different legal professionals and the authorities involved was held on the issue of transit, which have the expertise and knowledge of the subject, it is important to know different opinions and analysis. Graphical statistics through a sample taken gave real results, which allowed me to determine the solution to the problems in the Organic Law on Land Transportation, Traffic and Road Safety was held. In addition I was allowed to give recommendations by the findings of all the research work and especially propose the amendment to the Organic Law of Land Transport, Traffic and Road Safety, regarding the sentence of imprisonment for drivers for speeding outside the moderate range without causing human or material damage.